The Influence of Good Corporate Governance, Leverage, and Firm Size on the Integrity of Financial Statements: Pengaruh Good Corporate Governance, Leverage, Dan Firm Size Terhadap Integritas Laporan Keuangan - Fadilah, Nur Intan; Nurasik, Nurasik (Universitas Muhammadiyah Sidoarjo, 2022)
The world that is increasingly developing in the current era of globalization makes many new companies appear. This makes the competition tighter which can make the value of the company higher and make the company's performance also have to be further developed so that the integrity of the financial statements is one of the components used to assess the company's performance. In this case, GCG, Leverage, and Firm Size are very important to be implemented in the company in order to provide improvements to the integrity of financial statements and as added value for the company. Thus, the purpose of this study is to determine whether Good Corporate Governance, Leverage, and Firm Size affect the integrity of financial statements in Consumer & Goods Industry Companies Listed on the Indonesia Stock Exchange for the 2017-2020 period. In this research, the research used has a quantitative method, in this research the type of data used is secondary data through the technique of data collected by documentation, the sample used in this research is industrial food and consumer companies that are members of the Indonesia Stock Exchange in research conducted from 2017 to 2020. In taking samples using the purposive sampling method. The data analysis technique used in this research is descriptive statistical analysis, classical assumption test, and multiple linear regression analysis. The results of this study indicate that: (1) Independent Commissioner has an effect on the Integrity of Financial Statements. (2) The Audit Committee has an effect on the Integrity of Financial Statements. (3) Leverage affects the Integrity of Financial Statements. (4) Firm Size affects the Integrity of Financial Statements.